Penerapan Model Student Team Achievement Division (STAD) dalam Meningkatkan Kemampuan Menulis Teks Eksposisi Siswa di Sekolah Menengah Pertama - Supriadi, Supriadi; Jumriati, Jumriati; Wahab, Andi Wahyuningsih (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Makassar, 2023)
This study aims to find out the Student Team Achievement Division (STAD) model in Junior High School. The research program uses a qualitative approach with a type of class action research. The subjects in this study were class VIII students of SMP Negeri 25 Makassar totaling 35 students, consisting of 20 female and 15 male students. The procedure used in this study was to use cycles. Each cycle consists of four activities. The data collection method used is to use an instrument in the form of teks. Data is analyzed with descriptive statistical data analysis techniques. The results of this study show that the Student Team Achievement Division (STAD) is able to improve the ability to write student exposition texts. That result was obtained based on the average score of pranaksi students was 66.37. incycle I, the score increased to 72.4, and increased again in cycle II to 81.14.